2022
DOI: 10.1155/2022/4728921
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of Renal Function Damage in Patients with Essential Hypertension Based on Stepwise Regression Equation Scanning by AASI

Abstract: Detection of arterial stiffness is an important method to predict the occurrence of hypertension complications and to screen patients with high cardiovascular risk. In order to predict the damage of AASI to the renal function of patients with essential hypertension, the prediction of AASI based on stepwise Regression equation scanning for renal function damage in patients with essential hypertension is proposed. Measure the 24 h ambulatory blood pressure of the selected subjects, establish a linear Regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Plenty of studies are also similar to our findings. [27][28][29][30] What's more, some scholars also found that ABPM index, SUA level and microalbuminuria related to renal damage could be used as independent predictors of renal impairment in hypertensive patients. [31][32][33] Since our clinical data are limited, this may require additional researches with a larger sample size.…”
mentioning
confidence: 99%
“…Plenty of studies are also similar to our findings. [27][28][29][30] What's more, some scholars also found that ABPM index, SUA level and microalbuminuria related to renal damage could be used as independent predictors of renal impairment in hypertensive patients. [31][32][33] Since our clinical data are limited, this may require additional researches with a larger sample size.…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%